The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2196/27331
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbances in Frontline Health Care Workers During the COVID-19 Pandemic: Social Media Survey Study

Abstract: Background During the COVID-19 pandemic, health care workers are sharing their challenges, including sleep disturbances, on social media; however, no study has evaluated sleep in predominantly US frontline health care workers during the COVID-19 pandemic. Objective The aim of this study was to assess sleep among a sample of predominantly US frontline health care workers during the COVID-19 pandemic using validated measures through a survey distributed o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 38 publications
5
36
2
1
Order By: Relevance
“…5,6 Moreover, in comparison to the general population, health care workers are facing increased professional and personal responsibilities during the pandemic, which may lead to an additional psychological burden. 7 Multiple work stressors increase the risk of adverse mental health outcomes, including but not limited to psychological distress (fear, stress, anxiety, depression, exhaustion, post-traumatic stress disorder (PTSD)) and sleep dysfunction (poor sleep quality, sleep debt, insomnia). Indeed, during a crisis such as the current COVID-19 pandemic, the quality of sleep of health care workers becomes essential.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Moreover, in comparison to the general population, health care workers are facing increased professional and personal responsibilities during the pandemic, which may lead to an additional psychological burden. 7 Multiple work stressors increase the risk of adverse mental health outcomes, including but not limited to psychological distress (fear, stress, anxiety, depression, exhaustion, post-traumatic stress disorder (PTSD)) and sleep dysfunction (poor sleep quality, sleep debt, insomnia). Indeed, during a crisis such as the current COVID-19 pandemic, the quality of sleep of health care workers becomes essential.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 10 , 11 , 12 , 26 , 27 , 28 Several studies have determined that healthcare workers in particular experience sleep problems during the COVID‐19 pandemic. 4 , 14 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 The purpose of this study was to evaluate sleep quality and related factors among healthcare workers during the COVID‐19 pandemic in Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic and the accompanying lockdown have impacted many aspects of the daily life of adults, including sleep duration and quality [ 1 , 2 , 3 ]. For instance, a study on U.S. Americans showed that ~37% had increased sleep duration, whereas ~17% had decreased duration [ 2 ], and 45% reported a worsening of sleep quality in research on Italians [ 4 ].…”
Section: Introductionmentioning
confidence: 99%